Inclusão escolar no período de 2009 a 2013 sob a perspectiva das matrículas no censo escolar no Brasil - Castro, Vanessa Dias Bueno de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Regarding the laws, decrees and recent educational policies in search of a non-exclusive school, the present study aimed to analyze the effects of Política Nacional de Educação Especial na Perspectiva da Educação Inclusiva in relation to the number of enrollments of the target audience of special education in each Brazilian region, namely, North, Northeast, Southeast, South and Midwest, analyze the distribution of enrollments among the modalities of teaching and administrative offices from 2009 to 2013, using data obtained in Abstracts School Census Statistics and establish an overview of the scope of Política Nacional de Educação Especial na Perspectiva da Educação Inclusiva in relation to enrollments. It's a research descriptive type. The results obtained and presented indicate that enrollments in basic education have been reduced in all regions. In relation to the students target audience of special education, all regions recorded sequences of significant increases in enrollments in Common Regular Education Classes. The Special Classes of Regular Education suffered reductions in enrollment in all five regions. The enrollments in Exclusively Specialized Schools in it's turn, were reduced in the North, Northeast, Southeast and Midwest and expanded in the South, hence, unlike the other regions, this region has recorded increased enrollments in Systems Segregated of Education. As conclusions, we can point out that the work reinforces the importance of data processed as a means for panoramas on the enrollments of the target audience of special education and consequently as a basis for the development of educational laws and policies, despite its limits. The data presented in the survey indicate that demand has grown and can grow in the coming years if the school continues to exclude, and then, in an attempt to reverse it, seeks to include them again. Therefore, it's necessary to broaden the discussion and raise ...

Frente às legislações, decretos e políticas educacionais recentes, em busca de uma escola não excludente, o presente estudo teve por objetivos analisar os efeitos da Política Nacional de Educação Especial na Perspectiva da Educação Inclusiva em relação ao número de matrículas de alunos público-alvo da Educação Especial em cada Região brasileira, quais sejam, Norte, Nordeste, Sudeste, Sul e Centro-Oeste, analisar a distribuição dessas matrículas entre as modalidades de ensino e as dependências administrativas no período de 2009 a 2013, por meio dos dados obtidos nas Sinopses Estatísticas do Censo Escolar e estabelecer um panorama geral sobre o alcance da Política Nacional de Educação Especial na Perspectiva da Educação Inclusiva em relação às matrículas. Constitui-se em uma pesquisa de natureza descritiva. Os resultados obtidos e apresentados indicam que as matrículas na Educação Básica sofreram reduções em todas as Regiões. No que tange aos alunos público-alvo da Educação Especial, todas as Regiões registraram sequências de aumentos expressivos nas matrículas em Classes Comuns do Ensino Regular. As Classes Especiais do Ensino Regular sofreram reduções no número de matrículas nas cinco Regiões. As matrículas em Escolas Exclusivamente Especializadas, por sua vez, foram reduzidas nas Regiões Norte, Nordeste, Sudeste e Centro-Oeste e ampliadas na Região Sul, fazendo com que, diferentemente das outras Regiões, esta tenha contabilizado aumento nas matrículas em Sistemas Segregados de Ensino. Como conclusões, pode-se apontar que o trabalho desenvolvido reforçou a importância dos dados tratados, como meio para obter panoramas sobre as matrículas de alunos público-alvo da Educação Especial e, consequentemente, como base para a elaboração de leis e políticas educacionais, apesar de seus limites. Os dados apresentados pela pesquisa indicam que a demanda cresceu e pode crescer ...
Keywords: Educação; Educação inclusiva; Educação e Estado; Censo escolar; Education